SEROPREVALENCE OF TRANSFUSION TRANSMITTED INFECTIONS AMONG BLOOD DONORS – A CROSS SECTIONAL STUDY - POORANA PRIYA P; SUBHASHREE A.R. (International Journal of Pharma and Bio Sciences, 2013)
Transfusion of blood and blood components helps in saving millions of lives and also reduces morbidity. Blood transfusion is associated with transmission of infections and hence pre-transfusion screening of donors blood for presence of transfusion transmitted infections (TTI ) is essential. Seroprevalence study of transfusion transmitted infections among blood donors is valuable not only in providing information regarding the safety of blood transfusion but also to assess the prevalence of these infections in the local community. To study the Sero-prevalence of transfusion transmitted infections among blood donors at Department of Transfusion Medicine, Sree Balaji Medical College and hospital, Chennai for a period of about five years. The study was approved by the institutional ethical committee. A retrospective review of donor records covering the period 2008 to 2012 at the Department of Transfusion medicine, Sree Balaji Medical College and hospital, Chennai was carried out. Both Voluntary and replacement blood donors of both the sexes and all age groups were included in the study. Demographic data and screening details for TTI (HIV, HBsAg, HCV, Syphilis and Malaria) were tabulated and analyzed. During the study period of five years from 2008-2012, a total of 2294 blood donors were screened. Among them 97.7% were males and only 2.22% were females. The number of voluntary donors (2203 donors) was found to be higher than that of replacement donors (91 donors). Sero positivity for HBs Ag was found to be higher compared to other transfusion transmitted infections. VDRL positivity was showing an increasing trend. Our study showed that most of the donors were voluntary which is a welcome sign. Prevalence of Hepatitis B still ranked the highest among the donors indicating the need to increase the awareness of vaccination against this preventable TTI. The study also has prompted the recent rise in VDRL positivity among donors which could be an indirect indicator of unidentified HIV positivity; this mandates the need for strict donor selection criteria and more sensitive tests to screen for TTIs, particularly for HIV.